Autophagy plays a protective role as an anti‐oxidant system in human T cells and represents a novel strategy for induction of T‐cell apoptosis. Issue 8 (16th June 2014) - Watanabe, Ryu; Fujii, Hiroshi; Shirai, Tsuyoshi; Saito, Shinichiro; Ishii, Tomonori; Harigae, Hideo
<x xml:space="preserve">Abstract</x> Autophagy is an intracellular degradation system that plays an important role in T‐cell survival. However, the precise mechanism linking autophagy and cell death in primary human T cells is unclear because methods for monitoring autophagy in small numbers of primary human cells remain controversial. We established a novel method for assessing autophagy in activated human T cells using a retroviral GFP–LC3 expression system. We found that autophagy was induced after TCR stimulation and that autophagy‐defective naïve CD4+ T cells were susceptible to apoptosis through the intrinsic apoptotic pathway. Enhanced apoptosis of autophagy‐defective T cells resulted from accumulation of ROS due to impaired mitophagy. We also demonstrated that effector memory CD4+ T cells had lower autophagic activity than naïve CD4+ T cells, which contributed to their enhanced apoptosis due to increased ROS. Moreover, blocking autophagy increased intracellular mitochondrial volume and ROS levels in activated T cells. These results suggest a protective role of autophagy as an anti‐oxidant system in activated human T cells. The combination of an autophagy blocker and a mitochondrial electron transport chain inhibitor has a synergistic effect on T‐cell death, which could be a novel strategy for induction of T‐cell apoptosis.